Evaluation of Aqueous Leaf Extract +of Phyllantus Niruri in Vitro - Buba, Fatimah; Olaide, Habiba Adebayo; Abdulrahman, Ali Ali; Milala, Mohammed Adamu (Iraqi Journal of Science, 2023)
The toxicity effect of Chanca piedra (Phyllanthus niruri)leaves extract was studied on albino rats. Rats were divided into four groups, four per group. Group 1 received water and feeds only, whileonly. Groups 2, 3, and 4 were administered doses of the extract 200 mg/kg, 400 mg/kg, and 800 mg/kg body weight respectively. Parameters studied were indices of liver and kidney function. Results showed that final body weight, serum, AST, ALP, urea, Creatinine, and some electrolytes were not affected by the administration of the different doses of the extract. ALT significantly increased by administration of 200 mg/kg and 400 mg/kg of the extract when compared with the control. Besides, there was asignificant increase in the level of K+ (P>0.05) at the dose of 200mg/kg body weight of the extract. Similarly, Na+ was also significantly increased by the administration of the extract (400 mg/kg and 800 mg/kg). These increases observed may be due to the certain phytochemicals present in the extract. The longer administration of the extract could likely not to be safe.